Nonlinear optics Pulse propagation in fiber optics filled with gases, liquids, and organic dyes. (2019)
The characterization of nonlinear optical material properties, such as nonlinear refractive index and nonlinear absorption coefficient, is one of the most important subjects in nonlinear optics due to its application in many fields such as spectroscopy, material processing, biophysics, atmospheric sensing and metrology, among others. Besides the possibility of creating new technology. In this thesis, the Z-scan technique was implemented and calibrated. It remains one of the most widely used techniques to obtain both nonlinear refractive index and the absorption coefficient of a material. Moreover, nonlinear phenomena inside optical fiber is well known due to their applications and advantages like the low input energy required to generate supercontinuum, four wave mixing, dispersive wave, among others. In this work, several simulations were performed with new fiber geometries, material responses and different noble gases infiltrated in fiber. Different simulation regimes were considered as well by varying input power, pulse width and pressure. Nonlinear parameters for organic dyes, multi-walled carbon nanotubes, and CS2 were reported, pointing out the main reasons behind each result and addressing possible new phenomena involved. The nonlinear output response in both time and frequency domains was reported for several simulations, obtaining the nonlinear pulse output for the new CS2 response function. A novel consideration was proposed in which the final pulse depends on the propagation distance for non-instantaneous materials and the nonlinear constant (γ) must be recalculated at each step. It was demonstrated how the output pulse can be controlled by changing the fiber length. Among the most important results, it was found there exists a possibility to change between modulation instability and four wave mixing by only varying the propagation distance. Finally, it was also found that a special type of fiber, namely negative curvature hollow core fiber, can be used to obtain a broad band spectrum when it is filled with noble gases and they can be tuned with pressure from linear behavior up to a super critical zone.